Influence of gibberellic acid on seed germination and seedling emergence of Capsicum frutescens L. "Siling Labuyo" under heat stress - Edisan, Jadel H. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Germination and emergence of seeds are important stages of plant growth and development. However, its success for establishment and proliferation are regulated by both biotic and abiotic factors, and can be impacted by abiotic stresses (e.g., heat stress, drought, salinity). With climate change, these abiotic stresses are predicted to intensify, affecting the overall growth and development of many plant species, specifically economically important agricultural crops. Application of gibberellic acid (GA3) concentration promotes seed germination and aid in the emergence of plants under heat stress. This study employs a full factorial experiment (2 x 3 x 6) in a completely randomized design to determine the influence of gibberellic acid on the seed germination and seedling emergence of 􀂵siling labuyo􀂶 (Capsicum frutescens L.) under heat stress. Experimental factors include two heat treatment durations (3 and 6 hrs.), three GA3 concentrations (0, 100, and 500 ppm), and six temperature settings (25, 30, 35, 40, 45, and 50°C). Main effect of temperature and GA3 concentration is statistically significant on seedling emergence percentage (p = 0.0234), root (p = 0.0116) and leaf (p = 0.00245) length, and fresh weight (p = 0.000207); and seedling length (p = 0.0206). Interactive effect of temperature and GA3 concentration is statistically significant for seed vigour index (p = 0.0350) and seedling fresh weight (p = 0.0171). Cardinal temperatures for seed germination and seedling emergence are identified. Thermal range are from 18.95 to 23.97°C and 51.03 to 53.22°C for seed germination and seedling emergence, respectively, with optimal temperature ranging from 34.50 to 36.08°C. This study will be beneficial for farmers to have better cultivation practices and increased yield production for crops under heat stress. For researchers, it will become a baseline for studying the effect of GA3 application on growth and development of siling labuyo under heat stress.